Comparison study of different activity for image quality of nm/ct 670 pro system using lehr and megp collimators - Zamri, Ainin Zahraa (2025)
Single Photon Emission Computed Tomography (SPECT) remains a cornerstone in nuclear medicine for evaluating functional processes within the body. This study aims to compare the image quality of the GE Discovery NM/CT 670 Pro system using two types of collimators consist of Low Energy High Resolution (LEHR) and Medium Energy General Purpose (MEGP) which performs across different activity levels of technetium-99m (Tc-99m), specifically 7 mCi and 12 mCi point source. A NEMA 2012/IEC 2008 Image Quality Phantom was used to simulate clinical conditions. Parameters evaluated included sensitivity, spatial resolution (FWHM), signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR), with image reconstruction performed using the OSEM algorithm. The GE Discovery NM/CT 670 Pro Gamma Camera was employed for this study. Results demonstrated that MEGP collimators produced higher sensitivity at lower activity (7 mCi), while LEHR collimators consistently outperformed in terms of spatial resolution, SNR, and CNR, especially at higher activity (12 mCi). The findings highlight the trade-off between resolution and sensitivity based on collimator type and radiopharmaceutical activity. At higher activities, MEGP benefited from greater count collection but suffered from reduced image clarity due to scatter, whereas LEHR maintained superior image contrast and noise suppression. This study supports the importance of optimizing collimator choice and activity level based on clinical imaging goals. The results provide valuable insight for improving image quality, dose management, and diagnostic accuracy in SPECT imaging protocols.